The Influence of the Ruling Elite on Political Activity in the Conditions of Destructuring the Essence of the Philosophy of Law - Kelman, Mykhailo; Kristinyak, Myroslava; Andrusiak, Iryna; Panchenko, Sergii; Kelman, Rostyslav (Տիգրան Մեծ)
Different policy actors have different influences on the process. Most do not directly participate in political life: a particular layer of people called the political elite is more likely to get involved in it. From a philosophical point of view, the political elite is mainly defined as a minority of society, a somewhat independent, relatively privileged group (or a set of groups) that has the appropriate psychological, social and political qualities and is directly involved in the formation and implementation of political decisions related to the use of state power or influence on it. The main goal of the article is to characterise the negative influence of the ruling elite on the formation of political activity in the context of revealing its possibilities of destructuring the essence of the philosophy of law itself. The methodology was based on the main historical and theoretical research methods that made it possible to achieve the set goal. As a result of the study, the main elements of the negative influence of the ruling elite were characterised, its place in the philosophy of law was determined and which destructuring consequences it has.
Keywords: Philosophy of Law